Acceptance and commitment therapy for depression in chronic kidney patients: a pilot study - Diéguez, Sonia; García-Llana, Helena; Lobato, David; Marín, M. Teresa; Arenas, M. Dolores; Dapena, Fabiola; Montesinos, Francisco (Frontiers in Psychology, 2025)
Depression is a prevalent issue among patients with chronic kidney disease, particularly those undergoing hemodialysis. Its presence is associated with reduced quality of life, poor treatment adherence, and an increased risk of hospitalization and clinical deterioration. There is a pressing need for further research into effective psychological interventions aimed at improving the mental health of this population. This open-label pilot clinical trial involved five hemodialysis patients residing in Madrid who had been receiving treatment for over 3 months and exhibited clinically significant depressive symptoms. The intervention consisted of eight weekly, individual, 60-min face-to-face sessions based on a structured Acceptance and Commitment Therapy (ACT) protocol, delivered during dialysis. Outcomes were assessed using standardized questionnaires measuring quality of life, psychological symptoms, psychological inflexibility, and coping strategies at four time points: pre-treatment, post-treatment, and at 3- and 8-month follow-ups. A within-subject analysis was conducted, and the Reliable Change Index was applied to evaluate clinical significance. All participants completed the intervention, which was well accepted and deemed feasible, with high levels of satisfaction reported. Sustained reductions in depressive symptoms were observed in all participants, and improvements in quality of life were noted in three. No significant changes were found in psychological inflexibility or coping strategies. This pioneering pilot study in a Western context provides preliminary evidence supporting the feasibility and potential effectiveness of ACT for treating depression in hemodialysis patients. It highlights the viability of delivering psychological interventions within dialysis units and suggests ACT as a promising therapeutic approach for this population.